ZnO : Cu diluted magnetic semiconductor from pulsed filtered vacuum arc deposition - Cai, Yao Dong (2009)
Nowadays, there is considerable interest in the development of transition-metal-doped zinc oxide based DMSs because of their high Curie temperature(Tc)which is essential for spintronics. Because both ZnO and ZnO:Cu exhibit room temperature ferromganetism which is a essential characteristic for DMS, they have attracted much attention on the spintronic devices research. However, the mechanism of RT ferromganetism is controversial and unclear. In our work, a series of ZnO:Cu and ZnO films under different fabrication condition have been prepared by Pulsed Filtered Cathode Vacuum Arc technique using Zn:Cu alloy target and pure Zn target respectively. The structure of thin film is characterized by X-Ray Diffractometer (XRD) and the electrical property is also studied by Hall Effect Measurement. The room temperature ferromagnetism (RTFM) is observed by Alternating Gradient Magnetometer (AGM). For study of role of Cu, RT ferromagnetism were observed in both ZnO and ZnO:Cu thin films while ZnO:Cu film has larger magnetic moment. From XRD analysis, there is no effect on structural property by incorporation of Cu but the carrier concentration is increased obtained from Hall Effect measurement. In addition, samples under different oxygen flow rate, 28sccm, 43sccm and 70sccm, were fabricated. All of them exhibit RT ferromagnetism and oxygen does not have any impact to their structural i ii property. Sample with 28sccm flow rate possesses the largest magnetic moment and highest carrier concentration. Although sample with 70sccm has lower carrier concentration but its magnetic moment is larger than the one with 43sccm. We suspect this is due to partial oxidation of 43sccm sample as Zn cluster was found in 43sccm sample which does not contribute to magnetic property. Lastly, sample under 300oC was prepared. Compared to room temperature sample, its structure has changed but RT ferromagnetism is still observed but much smaller. The carrier concentration is also lower than the sample fabricated under room temperature. Hence, the origin of ferromagnetism in ZnO:Cu is greatly related to the carrier concentration.